(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: Estimation of stature is one of the important criterions for establishing the individuality of a person especially in cases of mutilated bodies and skeletal remains. With this in mind, this study has been undertaken to derive simple linear regression formulae and multiplication factors for calculating the stature from percutaneous measurements of ulna of both sides. Methods: The present study was carried out on 528 young and healthy individuals of age group 18-23 years. The body height and percutaneous length of ulna of both sides was measured separately and independent simple linear regression equations and multiplication factors were derived for both of the sexes. Results: It was found that males were having greater mean value of stature and ulnar length as compared to females. Simple linear regression equations and multiplication factors were derived from ulnar length in both sexes and direct relationship between ulnar length and the stature in both sexes was noted.